The Building Regulation for Resilience Program - Resilient Building Regulation in the Caribbean : 360° Resilience Background Paper - Benavidez, Melody Joy (World Bank, Washington, DC, 2021)
The Caribbean region’s exposure to natural disaster and climate events combined with population growth and urban development concentrated in highly risk prone Low Elevation Coastal Zones, leaves homes, people, and significant infrastructure assets highly vulnerable to disaster and climate impacts. Compounding this vulnerability is the prevalence of informal building and construction practices in the region. While many countries in the Caribbean have building codes in place, there remains a pervasive gap in the effective application of risk informed land use and adequate implementation and enforcement of building regulations (including building codes), all of which contributes to rising rates of informal, especially among poorer populations. Some of key contributing factors are under resourced regulators, lack of regulatory cooperation among relevant agencies, a lack of public awareness on the significant of compliance with building regulation, inadequate quality infrastructure services (e.g. testing and product certification) and insufficient political support for advancing this agenda. This confluence of factors often results in devastating disaster losses, as have been seen in countries like Dominica and the Bahamas in recent years. In Dominica, the low uptake of improved construction practices, weak enforcement of building codes, and the use of poor-quality construction materials left 90% of the country’s housing stock either partially damaged or destroyed in the aftermath of Hurricanes Irma and Maria in 2017. The damage amounted to US$353 million to the housing sector alone with Hurricane Maria estimated to have cost Dominica 225% of its GDP. The economic and human toll of disasters for the Caribbean is substantial. For some countries the damage exceeds the size of the economy, leaving huge reconstruction needs that can take years to be fully met. Effective building regulations ensure that builders and governments apply safe standards for the siting and construction of buildings so that they can withstand these events, protecting assets, their inhabitants and ultimately economic development. Recent disaster events in the Caribbean serve as a reminder of the urgent need to strengthen building regulation in the Caribbean as a means to reduce the vulnerability of the housing and building stock while increasing human and economic resilience. This note will broadly describe the current status of building regulation in the Caribbean, highlighting the biggest challenges to the implementation and enforcement of building codes, as well as proposing some solutions to overcome them.